What do we know about corporate governance, family ownership, and firm value? - Lestari, Dinda; Zirman; Hariyani, Eka; Oktari, Vera (JIFA (Journal of Islamic Finance and Accounting), 2022)
The purpose of this study was to obtain empirical evidence that the company's independent board of commissioners has a positive effect on firm value, to obtain empirical evidence that audit committees have a positive effect on firm value, to obtain empirical evidence that profitability has a positive effect on firm value, to obtain empirical evidence that family ownership strengthens good relations. Corporate governance on firm value and to obtain empirical evidence of family ownership strengthens the relationship between financial performance and firm value. Variable measurement in this study uses the dependent variable, independent variable, moderating variable, and control variable. The results of the study show that the board of commissioners and ROE have an effect on firm value. While the audit committee has no effect on firm value. And family ownership strengthens the relationship between ROE and audit committee on firm value, but cannot moderate the relationship between independent commissioners and firm value.